PROCEDURES IN THE VIETNAMESE TRANSLATION OF ENGLISH FAMOUS SAYINGS EXPRESSING FRIENDSHIP IN TERMS OF RHETORICAL DEVICES - LÂM, QUỐC THỊNH (ĐHNN, 2016)
This thesis is carried out with the aim of examining translation procedures that bring about the phenomenon of loss and gain of rhetorical device in the translating famous sayings expressing friendship from English into Vietnamese. 240 samples (120 English famous sayings expressing friendship and 120 their Vietnamese translation), were collected from books of famous sayings. Through the examination based on the qualitative and quantitative approaches, we discover that some of rhetorical devices used in famous sayings expressing friendship may be lost or gained in the translation process from English into Vietnamese. It is not unreasonable to believe that the translators employ translation procedures that have several effects on rhetorical devices in order to produce suitable translational versions. Finally, we hope that the results of the study could provide teachers and learners of English and Vietnamese with a better understanding of translation procedures in the Vietnamese translation of English famous sayings expressing friendship in terms of rhetorical devices, as well as giving some suggestions for further research and implications for language teaching and learning as well.
Keywords: TRANSLATION OF ENGLISH, RHETORICAL DEVICES